2014
DOI: 10.1016/j.ccr.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation Pathway Is Required to Maintain the Basal Breast Cancer Subtype

Abstract: SUMMARY The TFAP2C/AP-2γ transcription factor regulates luminal breast cancer genes and loss of TFAP2C induces epithelial-mesenchymal transition. By contrast, the highly homologous family member, TFAP2A, lacks transcriptional activity at luminal gene promoters. A detailed structure-function analysis identified that sumoylation of TFAP2A blocks its ability to induce the expression of luminal genes. Disruption of the sumoylation pathway by knockdown of sumoylation enzymes, mutation of the SUMO-target lysine of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 68 publications
7
96
0
Order By: Relevance
“…Overexpression of Tfap2a and Tfap2c mimics the mammary phenotype of RANK null mice (5,45,46). Tfap2a and Tfap2c maintain the luminal phenotype (28,29) and negatively regulate cancer stem cell markers (28). Although little is known about TFAP2B in mammary epithelia, our results suggest that, similarly to other members of the family, TFAP2B promotes luminal differentiation and is associated with good prognosis.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Overexpression of Tfap2a and Tfap2c mimics the mammary phenotype of RANK null mice (5,45,46). Tfap2a and Tfap2c maintain the luminal phenotype (28,29) and negatively regulate cancer stem cell markers (28). Although little is known about TFAP2B in mammary epithelia, our results suggest that, similarly to other members of the family, TFAP2B promotes luminal differentiation and is associated with good prognosis.…”
Section: Discussionmentioning
confidence: 55%
“…The AP2 transcription factor family is a set of retinoic acid inducible genes that governs the luminal epithelial phenotype in mammary development and carcinogenesis (28,29) and whose expression is associated with survival (30,31). Consistent with a tumor cell-luminal differentiation phenotype, GSEA analyses of the genes that characterize mammary differentiation hierarchy (20), revealed that the mature luminal upregulated set and the MaSC downregulated set, were overexpressed on the RANK-Fc-treated tumors (Fig.…”
Section: Rankl Negatively Regulates the Ap2 Transcription Factors Drmentioning
confidence: 84%
“…SUMOylation occurs in a highly dynamic manner in the cell and substrate proteins can be modified with either mono-or poly-SUMOylation. The SUMO pathway plays a critical role in cellular stress response, such as DNA damage, genomic stability, and heat shock (10)(11)(12), and it has also been recently implicated in prostate and breast cancer (13)(14)(15)(16). However, the role of this pathway in KRAS mutant cancers is not clear.…”
mentioning
confidence: 99%
“…The findings presented in Bogachek et al 9 offer a novel approach to the treatment of basal breast cancer and potentially other carcinomas in which the CD44 C/hi / CD24 ¡/low CSC population may be abrogated through inhibition of the SUMO pathway. Whereas conventional chemotherapy may preferentially eradicate the more differentiated tumor bulk, the addition of SUMO inhibitors may specifically target the CSC population, resulting in a more durable therapeutic response.…”
Section: Regulation Of Cancer Stem Cells By Sumoylationmentioning
confidence: 98%
“…One of the molecular characteristics of basal cancer is relatively high expression of CD44, a key marker of the CSC population, and TFAP2C has been shown to repress CD44 expression. 9 On the other hand, the highly homologous AP-2 family member TFAP2A lacks functional effects on luminal patterning. The molecular basis for functional specificity of the AP-2 family members depends upon sumoylation.…”
Section: Regulation Of Cancer Stem Cells By Sumoylationmentioning
confidence: 99%